A case: Rose Bengal test positive Crimean Congo hemorrhagic fever patient - Hatice Bozkurt Yavuz (Northwestern Medical Journal, 2023)
Brucella is one of the most common bacterial zoonosis. Crimean-Congo Hemorrhagic Fever (CCHF) is a potentially life-threatening infection. They have similar epidemiologic and clinical presentations. A 40-year-old male patient, engaged in animal husbandry, presented to the emergency unit with complaints of weakness, headache, and fever. Because of his low platelet count, he was referred to the internal medicine clinic. The patient did not have a history of contact with a tick or a CCHF patient. The Brucella Rose Bengal Test (RBT) was performed and the result was positive. After he was referred to the infectious diseases clinic, the CCHF RT-PCR test was found to be positive and the Brucella Wright agglutination test was negative. The patient, who was diagnosed with CCHF, was discharged in good condition. A positive RBT result does not always make a definitive diagnosis of Brucella infection. In areas where CCHF and Brucella are endemic, CCHF should be considered even if there is no history of ticks.